2021
DOI: 10.1155/2021/6616265
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Management of Cardiotoxicity in Hematologic Malignancies

Abstract: With the increasing overall survival of cancer patients due to recent discoveries in oncology, the incidence of side effects is also rising, and along with secondary malignancies, cardiotoxicity is one of the most concerning side effects, affecting the quality of life of cancer survivors. There are two types of cardiotoxicity associated with chemotherapy; the first one is acute, life-threatening but, fortunately, in most of the cases, reversible; and the second one is with late onset and mostly irreversible. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
1
16
0
4
Order By: Relevance
“…Direct or endogenous (e.g., AC)—also called primary cardiomyopathy—which is a consequence of the direct toxic effects of chemotherapy on the myocardium and is caused by myocardial cell loss, necrosis, and apoptosis mediated by oxidative stress [ 10 ].…”
Section: Cardiotoxicitymentioning
confidence: 99%
See 3 more Smart Citations
“…Direct or endogenous (e.g., AC)—also called primary cardiomyopathy—which is a consequence of the direct toxic effects of chemotherapy on the myocardium and is caused by myocardial cell loss, necrosis, and apoptosis mediated by oxidative stress [ 10 ].…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Late or chronic cardiomyopathy related to cumulative doses of AC, with an onset after more than 1 year and which is expressed as an arrythmia or LV dysfunction [ 10 ].…”
Section: Cardiotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Linschoten et al in their study observed two women who suffered from heart failure after months of receiving anticancer therapy. The genetic screening study witnessed mutations in TTN, encoding the myofilament titin responsible for the occurrence of heart failure [ 153 ].…”
Section: Genes’ Susceptibility To Cardiotoxicity Induced By Chemotherapeutic Agentsmentioning
confidence: 99%